To solve the equation
\[ 3m + \frac{5}{4} - \frac{3m}{4} = -2, \]
let's first combine the terms involving \(m\) on the left side.
We can do this by rewriting \(3m\) as a fraction with a common denominator of 4:
\[ 3m = \frac{12m}{4}. \]
Now, substituting back into the equation gives us:
\[ \frac{12m}{4} - \frac{3m}{4} + \frac{5}{4} = -2. \]
We can combine the terms with \(m\):
\[ \frac{12m - 3m + 5}{4} = -2. \]
This simplifies to:
\[ \frac{9m + 5}{4} = -2. \]
Next, we can eliminate the fraction by multiplying both sides of the equation by 4:
\[ 9m + 5 = -8. \]
Now, isolate \(9m\) by subtracting 5 from both sides:
\[ 9m = -8 - 5, \]
which simplifies to:
\[ 9m = -13. \]
Lastly, divide both sides by 9 to solve for \(m\):
\[ m = -\frac{13}{9}. \]
Thus, the value for \(m\) that makes the equation true is
\[ \boxed{-\frac{13}{9}}. \]